Manivestasi Konsep (Sunatullah) Dalam Pendidikan (Suatu Kajian Teologis) - Sutarjo, J; Ahmad, Nurwadjah; Suhartini, Andewi (Tarbawiyah Jurnal Ilmiah Pendidikan, 2020)
One object of study of God is God's order for humans, commonly known as Sunatullah. Allah SWT as a substance that is the creator of all beings both human and the entire universe is one of the regularities of Allah SWT. Furthermore, the phenomenon of the order of God Almighty in His creation can be seen starting from the creation of humans and nature and their contents. In the level of theology, God's order for human beings (Sunatullah) is not limited to the regularities possessed by His creatures, but more than that, the various regularities that occur in creatures are the will of Allah SWT. Allah Almighty is the substance that wills, and controls the order in His creatures. Sunnatullah as a concept should be invested in Islamic education. Therefore it is necessary to understand about sunnatullah as something that must be believed, used as guidelines and translated at the level of education. After being translated into the education curriculum, the next task of education is to implement sunnatullah as a theological concept into a practical action for students.